2014
DOI: 10.1017/s1041610214000969
|View full text |Cite
|
Sign up to set email alerts
|

Preferences regarding disclosure of a diagnosis of dementia: a systematic review

Abstract: The vast majority of individuals without and with cognitive impairment prefers to be informed about a diagnosis of dementia for reasons pertaining to autonomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 50 publications
5
57
0
1
Order By: Relevance
“…However, we know that the diagnostic rates of dementia, although improving, 70 are low. 71 Furthermore, although the majority of people with dementia wish to know the diagnosis, 72 GPs can be reluctant to fully disclose it. 12,73,74 Secondly, GPs may be reluctant to initiate a conversation about BPSD unless they feel comfortable giving practical advice to family caregivers on managing BPSD, something many GPs struggle with.…”
Section: Discussionmentioning
confidence: 99%
“…However, we know that the diagnostic rates of dementia, although improving, 70 are low. 71 Furthermore, although the majority of people with dementia wish to know the diagnosis, 72 GPs can be reluctant to fully disclose it. 12,73,74 Secondly, GPs may be reluctant to initiate a conversation about BPSD unless they feel comfortable giving practical advice to family caregivers on managing BPSD, something many GPs struggle with.…”
Section: Discussionmentioning
confidence: 99%
“…Several can be rapidly administered as screening tests in the outpatient general practice setting such as the widely used mini-mental status examination and Functional Activities Questionnaire and even tests that focus on more specific cognitive deficits, such as verbal fluency and the Digit Symbol Substitution test. Unfortunately, studies have shown that general practitioners have a low sensitivity for detection of dementia, particularly mild dementia, lower than what is reported for specialty memory centers (8,22). However, even in a memory center setting, neurocognitive testing has moderate sensitivity and specificity, with estimates of about 70% each (22).…”
Section: Current Status Of Tests For Admentioning
confidence: 89%
“…Therefore, AD represents an increasingly common and debilitating disease with subsequent heavy financial and societal burden on a global scale. It is no surprise that there is great demand for a predictive test from patients and physicians alike (8). However, the push for diagnosis at earlier milder stages of disease, where clinical presentations of various syndromes are often overlapping, also pushes the limits of current clinical testing and diagnostic imaging modalities, dominated by structural magnetic resonance imaging (MRI) and fluorine 18 radioisotope label [F-18] fluorodeoxyglucose (FDG) positron emission tomography (PET; Fig 1).…”
mentioning
confidence: 99%
“…Previous authors have shown that the majority of patients prefer a timely diagnosis. 47,48 Furthermore, MCs can still offer much to patients in the past for being unclear about whether they were running projects or contributing to regional health services. 50 Currently, MCs are no longer isolated facilities that focus solely on conducting research.…”
Section: Treatmentmentioning
confidence: 99%